2023
DOI: 10.7554/elife.82843
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia truncates and constitutively activates the key cholesterol synthesis enzyme squalene monooxygenase

Abstract: Cholesterol synthesis is both energy- and oxygen-intensive, yet relatively little is known of the regulatory effects of hypoxia on pathway enzymes. We previously showed that the rate-limiting and first oxygen-dependent enzyme of the committed cholesterol synthesis pathway, squalene monooxygenase (SM), can undergo partial proteasomal degradation that renders it constitutively active. Here, we show hypoxia is a physiological trigger for this truncation, which occurs through a two-part mechanism: (1) increased ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 70 publications
3
15
0
Order By: Relevance
“…Cholesterol metabolism represents an important drug targeting pathway (8, 9). Targeting this highly oxygen-dependent pathway can also alter other physiological processes (10, 11)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cholesterol metabolism represents an important drug targeting pathway (8, 9). Targeting this highly oxygen-dependent pathway can also alter other physiological processes (10, 11)…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol metabolism represents an important drug targeting pathway (8,9). Targeting this highly oxygen-dependent pathway can also alter other physiological processes (10,11) Much less is known about the functions of non-polar sterols from the late part of cholesterol synthesis (sterol intermediates) that are structurally similar to cholesterol (See Supp. Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both responses depend on the lipid-sensing N-terminal regulatory domain of SM (SM-N100), which is embedded in the ER membrane. Accumulated squalene also promotes the partial rather than complete proteasomal degradation of SM, disrupting the SM-N100 domain and liberating a long-lived and constitutively active enzyme variant (truncated SM or trunSM) ( 9 , 10 ). Previous work showed that SM truncation is stimulated during hypoxia, which preserves enzymatic activity and downstream flux through cholesterol synthesis to maintain cell viability ( 10 , 11 ).…”
mentioning
confidence: 99%
“…Accumulated squalene also promotes the partial rather than complete proteasomal degradation of SM, disrupting the SM-N100 domain and liberating a long-lived and constitutively active enzyme variant (truncated SM or trunSM) ( 9 , 10 ). Previous work showed that SM truncation is stimulated during hypoxia, which preserves enzymatic activity and downstream flux through cholesterol synthesis to maintain cell viability ( 10 , 11 ). However, other functional or directly pathophysiological consequences await discovery.…”
mentioning
confidence: 99%